LGG-35. FUNCTIONAL GENOMIC APPROACHES TO IDENTIFY THERAPEUTIC TARGETS IN MYB AND MYBL1 EXPRESSING PEDIATRIC LOW-GRADE GLIOMAS. (4th December 2020) - Condurat, Alexandra-Larisa; Wefers, Annika; Gonzalez, Elizabeth; Doshi, Jeyna; Khadka, Prasidda; Jessa, Selin; Tsai, Jessica; Buchan, Graham; Rouleau, Cecile; Abid, Tanaz; Goodale, Amy; Persky, Nicole; et al.
Abstract: AIM: Recurrent structural variants involving MYB and MYBL1 transcription factors were recently identified in pediatric low-grade gliomas (pLGGs), such as the MYB-QKI rearrangement in Angiocentric Gliomas and truncations of MYBL1 ( MYBL1tr ) in Diffuse Astrocytomas. However, therapeutic dependencies induced by these alterations remain unexplored. METHODOLOGY: We have generated in vitro pLGG mouse neural stem cell (NSCs) models engineered to harbor distinct MYB/MYBL1 genomic alterations. We used single cell RNA sequencing approaches to determine the transcriptional profile and dissect the central regulatory networks of our in vitro pLGG models over time. To identify specific genetic dependencies associated with MYB/MYBL1 mutations, we employed the Brie genome-wide mouse CRISPR lentiviral knockout pooled library, consisting of 78, 637 single guide RNAs (sgRNAs) targeting 19, 674 mouse genes. RESULTS: MYB/MYBL1 expression in neural stem cells induced activation of cell-cycle related, glioma-related and senescence-related pathways that are involved in normal development, including activation of MAPK and mTOR signaling which are also activated in human pLGG samples. Genome-scale CRISPR-cas9 screens in isogenic NSCs expressing MYB-QKI or MYBL1tr identified differential genetic dependencies relative to GFP controls. These included regulators of cell-cycle progression and several modulators of the ubiquitin-proteasome degradation pathway. Analysis of RNA-sequencing data from human tumors revealed several of these dependencies identified in the cell line model to be differentially expressed in MYB -altered pLGG tumors relative to normal brain. CONCLUSION: Expression of MYB family alterations induces expression of key developmental and oncogenic pathways and genetic dependencies that represent potential therapeutic targets for MYB or MYBL1 rearranged pLGGs.